Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1289/ehp.8197
|View full text |Cite
|
Sign up to set email alerts
|

Workgroup Report: Biomonitoring Study Design, Interpretation, and Communication—Lessons Learned and Path Forward

Abstract: Human biomonitoring investigations have provided data on a wide array of chemicals in blood and urine and in other tissues and fluids such as hair and human milk. These data have prompted questions such as a) What is the relationship between levels of environmental chemicals in humans and external exposures? b) What is the baseline or “background” level against which individual levels should be compared? and c) How can internal levels be used to draw conclusions about individual and/or population health? An in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Bates and colleagues' report on a workshop to discuss biomonitoring study design, interpretation and communication concluded that a website should be a high priority, enabling the data to be shared with other scientists (Bates et al, 2005). Researchers also have an obligation to the participants and the general public to be transparent and honest about the design and implementation of the study as well as how the results and other outputs will be used.…”
Section: Discussionmentioning
confidence: 99%
“…Bates and colleagues' report on a workshop to discuss biomonitoring study design, interpretation and communication concluded that a website should be a high priority, enabling the data to be shared with other scientists (Bates et al, 2005). Researchers also have an obligation to the participants and the general public to be transparent and honest about the design and implementation of the study as well as how the results and other outputs will be used.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers typically use the peer-reviewed scientifi c literature as the principal approach to communicate study results [ 61 ]. On the other hand, researchers are increasingly called upon to communicate with study subjects when designing, interpreting, and reporting their work [ 62 ].…”
Section: Results Communicationmentioning
confidence: 99%
“…Overall, in result communication there must be a great concern on the subject's ability to understand study information, including the associated uncertainties and limitations; pamphlets, posters, graphic narratives, and videos may prove to be useful to reach a wider audience [ 61 ].…”
Section: Results Communicationmentioning
confidence: 99%
“…Experimental studies with pesticides and other industrial products are often controversial, particularly when nonpharmaceuticals (such as pesticides) are intentionally administered to humans, regardless of potential study benefits (Bates et al 2005;Boxer and Waxman 2005;Kaiser 2003). Controversy surrounded a human volunteer study (Cain 2004) performed on the irritant effects of chloropicrin (Lee and Clark 2005).…”
Section: Volunteer Studiesmentioning
confidence: 99%